2022
DOI: 10.1186/s12891-022-05709-8
|View full text |Cite
|
Sign up to set email alerts
|

Arthro-Broström with endoscopic retinaculum augmentation using all-inside lasso-loop stitch techniques

Abstract: Background There is still some controversy about the augmentation of the inferior extensor retinaculum after arthroscopic anterior talofibular ligament repair. The aim of this study was to evaluate the novel arthro-Broström procedure with endoscopic retinaculum augmentation using all-inside lasso-loop stitch techniques for chronic lateral ankle instability. Methods Thirty-four cases with grade-2 or grade-3 chronic anterior talofibular ligament lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Improved repair of the inferior extensor retinaculum provides initial protection and improved repair of the ATFL for the rotational function of the joint ( Dalmau-Pastor et al, 2018 ). In addition, inferior extensor retinaculum augmentation may be performed using the total inner gloving technique to avoid nerve injury ( Yang et al, 2022 ). In 2019, Vega et al ( Vega et al, 2020 ) performed total arthroscopic ATiFL-DF transfer enhancement using five fresh-frozen ankle joint specimens and reported that transfer via the anterior-lateral portal did not harm the superficial peroneal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Improved repair of the inferior extensor retinaculum provides initial protection and improved repair of the ATFL for the rotational function of the joint ( Dalmau-Pastor et al, 2018 ). In addition, inferior extensor retinaculum augmentation may be performed using the total inner gloving technique to avoid nerve injury ( Yang et al, 2022 ). In 2019, Vega et al ( Vega et al, 2020 ) performed total arthroscopic ATiFL-DF transfer enhancement using five fresh-frozen ankle joint specimens and reported that transfer via the anterior-lateral portal did not harm the superficial peroneal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Both the arthroscopic Lasso-loop stitch technique and arthroscopic Broström-Gould technique have been commonly used to treat CLAI patients, and multiple studies have reported satisfactory outcomes in terms of postoperative clinical and functional scoring [31,41]. Rigby et al reported 30 CLAI patients receiving the arthroscopic outside-in Broström-Gould technique, with the average postoperative VAS pain score decreasing from 8.2 to 1.5 and AOFAS score improving from 35.1 to 95.3 [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, 20%-40% of patients are prone to progress to chronic lateral ankle instability (CLAI), leading to persistent pain, recurrent sprains and repeated episodes of the ankle giving way [37,38]. The modified Broström procedure has been widely accepted as the gold standard for operative treatment of CLAI [39], and various arthroscopic Broström surgeries have been published [4,6,9,17,24,28,41] demonstrating feasible clinical outcomes [6,17,38,44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Line anchors enhance ATFL repair and lays a solid foundation for postoperative healing and early high-intensity rehabilitation exercise programs. Arthroscopic arthro-Broström supported band enhancement using the all-medial lasso loop suture technique avoids nerve injury and does not interfere with subtalar joint stability[ 67 ]. With the rapid emergence of new technology, in the future, we may need to explore and utilize the advantages of various surgical techniques and treatment management tools[ 68 ].…”
Section: Management Measuresmentioning
confidence: 99%